Strategi Marketing Politik Caleg Perempuan Dalam Pemilihan Legislatif Tahun 2019 (Jurnal Nawala Politika, 2022)
The struggle of women in politics has gone through a long process. After struggling to overcome gender. Now the discourse of women in politics shifts to present women in quantity. This study aims to find out how the political marketing strategy of female legislative candidates is with a case study of Ni Made Rahayuni's victory in the Tabanan DPRD Pileg 2019. Success in political events is certainly inseparable from the political strategies used by candidates. Adopting concepts from political marketing theory. By using qualitative methods through interviews, the results of the research are as follows: First, through political marketing directly to the public, the use of mass media, and third parties. Second, where the women's programs offered play a good role in political marketing as a product and a promotional tool. Third, beauty efforts to be in the spotlight in the future can become a political marketing strategy that led Mrs Ni MadeRahayuni to win the event.